Empowering Urban Community in Kediri through Training to Convert Used Cooking Oil into Eco-Friendly Soap - Nina Lisanty; Wiwiek Andajani; Yusuf Santoso; Yudha Saputra; Azzahra Amalia (Universitas Sebelas Maret, 2025)
This paper discusses waste management in urban areas, with a focus on household liquid waste. Households are the largest contributors to waste in Indonesia, and cities tend to generate more waste than rural areas. Waste management in urban areas involves the stages of collection, sorting, recycling, composting, burning, and public education. The community service team from the Faculty of Agriculture, University of Kadiri, initiated educational activities and training in household liquid waste management, especially used cooking oil, in Kediri City. This activity aimed to educate urban communities, especially Persada Sayang Housing residents, in managing household liquid waste into soap products. Residents of Persada Sayang Housing were chosen as the target community because they live right in the middle of Kediri City and are active in managing household waste as evidenced by the existence of a Bank Sampah there. This activity involved the process of identifying needs, program planning, resource mobilization, program implementation, evaluation, and coaching to ensure program sustainability. By actively involving the community in every stage of liquid waste management, the waste management program in urban areas could be more effective and sustainable and have a significant impact on the communities served. In efforts to manage waste in urban areas, cooperation between the government, waste management agencies, and the community is crucial. The government and various parties must continue to work to increase awareness and implement good waste management practices, such as waste reduction, recycling and efficient processing.